Degradation of Lake Ziway, Ethiopia: A study of the environmental perceptions of school students. Issue 4 (December 2015) - Desta, Hayal; Lemma, Brook; Albert, Gerhard; Stellmacher, Till
Abstract: Lake Ziway in Ethiopia is a freshwater lake supporting multitude uses, including irrigation, fishing, water supply and recreation. However, the lake is being degraded primarily because of various land‐ and water‐use activities in its watershed. Recognizing these human impacts on the lake's water quality and quantity, the perceptions of school students were surveyed under the belief that the future of the lake is largely dependent on this younger generation. The goal of this study was to better understand how students actually recognize the extent to which various human activities impact the water quantity and quality of Lake Ziway. As major stakeholders in their communities, the perceptions of school students from four high schools regarding the changes to the lake over time were investigated. Students were contacted by purposive sampling, based on criteria of student academic performances, and their proximity to the lake. Their perceptions were studied on the basis of an interview survey. The majority of students indicated that high levels of human activities, especially water abstractions and water pollution, were the main lake impacts. Students believe there is a lack of sustainable utilization and protection of the lake. They suggested coordinated activities among all lake stakeholders in the participation and decision‐making process to properly manage the lake. Provision of awareness to both local administrations and local communities, concern for establishing an appropriate regulatory body and allocating a sufficient budget, and strict controls on flower farm practices in the lakeshore, also was considered to be of high priority as a means of conserving the sustainability of the lake. The result derived from this survey has important implications for facilitating improved school curricula, and for federal, regional and district level water resource management authorities, in setting priorities and developing policies for the sustainability of Lake Ziway.